Associations of cardiovascular disease morbidity and mortality in the populations watching major football tournaments: A systematic review and meta-analysis of observational studies. Issue 12 (March 2020) - Wang, Huajun; Liang, Lunchang; Cai, Ping; Zhao, Jianli; Guo, Lan; Ma, Huan
Abstract: Background: Whether or not increased hospitalizations and/or deaths due to cardiovascular disease during major football tournaments (MFTs) remains controversial. We undertook a systematic review and meta-analysis of published studies to assess the relationships of cardiovascular events and MFTs. Methods: Observational studies reporting relationship of cardiovascular disease morbidity and mortality with MFTs during the days of games or within 2 weeks after game season were included. Relative risk ratios (RR) with 95% confidence interval (CI) were pooled and analyzed using a random/fixed-effects model. Results: Nineteen cross-sectional observational studies that examined the association between MFTs and non-fetal cardiovascular events and mortality were found to be eligible from 3419 references, for inclusion in the systematic review and meta-analysis. Of the 10 studies reported hospitalizations due to non-fetal acute cardiovascular events, the pooled RR was 1.17 (95% CI 1.01–1.36). Of the 10 studies reported cardiovascular mortality the pooled RR was 1.03 (95% CI 1.00–1.05). Of the studies examining the mortality, 6 studies reported the lost or win of the national team. Pooling of four studies where their national teams lost the MFTs produced a RR for the mortality of 1.19 (95% CI: 1.09–1.30), and 4 studies of the 6 whose national teams won produced a pooled RR for cardiovascular mortality of 0.88 (0.79–0.98). Conclusion: This systematic review and meta-analysis showed an increased risk of hospitalization due to non-fetal acute cardiovascular events and cardiovascular mortality with watching MFTs. Abstract : Supplemental Digital Content is available in the text